The highs and the lows: Bank failures in Sweden through inflation and deflation, 1914-1926 - Sean Kenny; Anders Ögren; Liang Zhao (Queen's University Centre for Economic History (QUCEH), 2023)
This paper revisits the Swedish banking crisis (1919-26) that materialized as post war deflation replaced wartime inflation (1914-18). Inspired by Fisher's 'debt deflation theory', we employ survival analysis to 'predict' which banks would fail, given certain ex-ante bank characteristics. Our tests support the theory; maturity structures mattered most in a regime of falling prices, with vulnerable shorter-term customer loans and bank liabilities representing the most consistent cause of bank distress in the crisis. Similarly, stronger growth in i) leverage, ii) weaker collateral loans and iii) foreign borrowing during the boom were all associated with bank failure in post-war Sweden (1919-26).
Keywords: E58; G01; G21; G28; N24; 330; banking crisis; survival analysis; early warning indicators; debt deflation; maturity mismatch; Sweden